2004
DOI: 10.1007/s00406-004-0523-0
|View full text |Cite
|
Sign up to set email alerts
|

Prepulse inhibition of the acoustically evoked startle reflex in patients with an acute schizophrenic psychosis—A longitudinal study

Abstract: Deficits in sensorimotor gating as assessed by prepulse inhibition (PPI) of the startle reflex have been reported in schizophrenia. However, the state or trait nature of these deficits and the relationships with clinical features and psychopathological symptoms are not clear. To explore these issues, we performed a longitudinal study with schizophrenia inpatients. We examined 36 medicated schizophrenia inpatients twice in the course of an acute psychotic episode: recently after admission and after psychopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 46 publications
9
41
0
1
Order By: Relevance
“…In one of our studies, schizophrenia patients with lower PPI capacity also showed lower attentional performance scores on the CANTAB rapid visual information processing (RVP) task than those with higher PPI levels (Ludewig et al, 2003b). Similarly, other studies found that PPI deficits in schizophrenia are correlated with thought disorder (Meincke et al, 2004;Perry and Braff, 1994;Perry et al, 1999). Furthermore, the finding of a positive correlation between PPI capacity and attentional performance in the present study is also of relevance to the view that a serotonergic dysfunction may contribute to the pathophysiology of cognitive deficits in schizophrenia (Meltzer and Nash, 1991;Roth et al, 2004).…”
Section: Discussionsupporting
confidence: 71%
“…In one of our studies, schizophrenia patients with lower PPI capacity also showed lower attentional performance scores on the CANTAB rapid visual information processing (RVP) task than those with higher PPI levels (Ludewig et al, 2003b). Similarly, other studies found that PPI deficits in schizophrenia are correlated with thought disorder (Meincke et al, 2004;Perry and Braff, 1994;Perry et al, 1999). Furthermore, the finding of a positive correlation between PPI capacity and attentional performance in the present study is also of relevance to the view that a serotonergic dysfunction may contribute to the pathophysiology of cognitive deficits in schizophrenia (Meltzer and Nash, 1991;Roth et al, 2004).…”
Section: Discussionsupporting
confidence: 71%
“…Of particular interest in this regard is a cross-sectional study indicating that clozapine treatment, relative to typical antipsychotic treatments, is associated with reduced PPI deficits in patients with schizophrenia (Kumari et al, 1999). While the evidence indicating that second-generation antipsychotics, especially clozapine, may ameliorate PPI deficits in schizophrenia is based largely on cross-sectional studies (Kumari et al, 1999;Hagan and Jones, 2005), some longitudinal studies are now suggesting that PPI deficits may be reversed in groups of schizophrenia patients treated primarily with second-generation compounds (Meincke et al, 2004). Although much more work is needed to clarify the effects of newer antipsychotics on both cognitive and PPI deficits in schizophrenia, it is clear that first-generation anti-psychotics fail to normalize either class of deficits.…”
Section: Prepulse Inhibition Models In Animals Using Prepulse Inhibitmentioning
confidence: 99%
“…On the other hand, several studies have failed to show PPI-enhancing effects of either typical or atypical medication in schizophrenia patients (Duncan et al, 2003a, b;Perry et al, 2002;Mackeprang et al, 2002), even though Duncan et al (2003b) found an improvement of clinical symptoms with atypical medication. In contrast to these negative findings, a recent study showed that an enhancement of PPI is associated with symptom reduction in patients treated for schizophrenia with either typical or atypical antipsychotic treatments (Meincke et al, 2004). Although it appears that atypical antipsychotics may be superior in normalizing PPI, the literature to date is inconclusive regarding the impact of antipsychotic medication on PPI.…”
Section: Introductionmentioning
confidence: 96%